أبعاد التسويق بالعلاقات و تأثيره في تحقيق ولاء الزبون-دراسة حالة مؤسسة اتصالات الجزائر - زياني, نجية (جامعة الوادي - University of Eloued, 2023)
إن الهدف الأساسي من هذه الدراسة هو التعرف على التسويق بالعلاقات ودوره في تحقيق وبناء الولاء لدى الزبون بمؤسسة اتصالات الجزائر بتلمسان عن طريق استخدام مقياس وأبعاد التسويق بالعلاقات الذي يتكون من ستة أبعاد هي: (الاتصال، الالتزام، الثقة، التعاطف، التبادلية، القيم المشتركة) اعتمدنا في هذه الدراسة على المنهج الوصفي التحليلي، كما استخدمنا الاستبانة كأداة لجمع المعلومات والبيانات من أفراد العينة، بحيث بلغ عددهم 100. أظهرت نتائج الدراسة عن وجود ولاء لدى الزبائن بالخدمات المقدمة من طرف مؤسسة اتصالات الجزائر فرع تلمسان وفقا لأبعاد جودة التسويق بالعلاقات المدروسة. The research aims to identify the relationship marketing and its role in achieving and building customer loyalty at the Algeria Telecom in Tlemcen by using the relationship marketing scale and dimensions, which consists of six dimensions: (communication, commitment, trust, sympathy, reciprocity, common values). ,In this study, we relied on the descriptive analytical approach, and we also used the questionnaire as a tool for collecting information and data from the sample members, so that their number reached 100. The results of the study showed that customers have loyalty to the services provided by the Algeria Telecom in Tlemcen
Dimensions of relationship marketing and its impact on achieving customer loyalty - a case study of Algeria Telecom Corporation
مقال
Keywords: ولاء الزبون ; التسويق بالعلاقات ; أبعاد التسويق بالعلاقات ; إدارة العلاقة مع الزبون